Spherocytosis in Newborn Secondary to Novel Heterozygous Mutation in Gene: Case Report - Daphna Varadi MD; Benjamin Caplan MD; Maria Scarano PhD; Rafat Ahmed MD (SAGE Publishing, 2023)
This case report describes a novel mutation of the SPTB gene as a potential pathogenic cause of spherocytosis. A 3-week-old male presented with clinical and laboratory signs consistent with hemolytic spherocytosis, including jaundice, hyperbilirubinemia, anemia, reticulocytosis, negative Coombs test, no ABO or Rh incompatibility, and a peripheral blood smear notable for numerous spherocytes. His laboratory work demonstrated persistent anemia despite daily folate prompting next-generation sequencing which revealed a novel mutation in the SPTB gene resulting in a nonfunctioning protein product. Correlation of the genetic finding with clinical presentation may help guide management for this and future patients.